CHARACTERISTICS OF FRESHWATER MUSSEL SHELL (Pilsbryoconcha sp.) COLLAGEN ORIGINATING FROM SUNGAI PAKU WATERS EXTRACTED WITH DIFFERENT ACETIC ACID CONCENTRATIONS - Pipit Pasaribu; N Ira Sari; Dian Iriani (Berkala Perikanan Terubuk, 2021)
This study was aimed to determine the characteristics of freshwater mussel shell collagen originating from Paku river waters extracted with different concentrations of acetic acid and to determine the best concentrations of acetic acid to produce the highest collagen yields. The different concentration of acetic acids to produce collagen was 0.50 M, 0.75 M and 1 M. The parameters of the analysis observed were collagen yield, proximate analysis (moisture, ash, fat, and protein content), pH and heavy metal analysis (Pb and Cd). The use of 0.50 M acetic acid concentration was the best concentration to produce collagen with the characteristics of a yield value of 18.76%, a moisture content value of 6.64%, ash content value of 82.60%, fat content value of 0.28%, protein content value of 6.81%, a pH value of 6.77, The heavy metal content of Pb 0.53 mg/kg and Cd 0.07 mg/kg.